Learning Transformation in the Digital Era: A Literature Review on Innovations in Teaching Methods and Media - Risnawati, Yun; Hendra, Muhammad; Lestari, Nana Citrawati; Apriliyani, Eka Suci; Arsyad, Muhammad; Efrina, Gusnita (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The transformation of learning in the digital era has brought significant changes to teaching methods and educational media across various levels of education. This article aims to review the literature on innovations in digital learning methods and media, identify the challenges faced, and explore opportunities for developing more effective and contextually relevant learning approaches. The method employed is a qualitative literature review with content analysis of 30 scholarly sources systematically selected from reputable databases. The findings indicate that digital learning innovations such as blended learning, flipped classrooms, and the use of interactive media positively contribute to student engagement and learning outcomes. However, the implementation of these transformations still faces obstacles, including limited teacher competencies, unequal infrastructure, and a lack of systematic policy support. This study emphasizes that the digital transformation of learning must be accompanied by a shift in pedagogical paradigms and institutional support to ensure that technology is meaningfully optimized. Accordingly, this research provides a scientific foundation for developing inclusive and sustainable digital learning strategies for the future.